Integritas Laporan Keuangan Melalui Kualitas Audit Sebagai Variabel Moderasi: Dewan Komisaris Independen, Ukuran Perusahaan dan Leverage - Putri, Nabila Ulfa Maharani; Yeni, Fitri; Crefioza, Omia (Juara: Jurnal Riset Akuntansi, 2024)
This study investigates how independent board of commissioners, company size and leverage influence the integrity of financial reports using audit quality as a moderator. The focus is on non-cyclical consumer sector entities listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022, with a sample of 62 companies using a purposive sampling approach. Panel data regression analysis was employed as the analytical method using SPSS 26. The study findings show that an independent board of commissioners has a positive impact on the integrity of financial reports, company size has a negative impact on the integrity of financial reports, as does leverage. Furthermore, audit quality is able to moderate the relationship between the independent board of commissioners, company size, variable leverage and the integrity of financial reports.